The Influence of Corporate Governance and Corporate Profitability on Corporate Value with CSR Disclosure as a Mediator - Dewi Regita Cahyanti; Indraswari, Citra Rahayu (Contemporary Studies in Economic, Finance and Banking, 2025)
This study is based on the importance of enhancing Corporate Value through sound governance practices and strong profitability, while considering the role of Corporate Social Responsibility (CSR) disclosure as a mediating mechanism. The study aims to analyze the influence of Corporate Governance and Corporate Profitability on Corporate Value, as well as to examine the mediating role of CSR disclosure in these relationships. A quantitative approach was employed using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method, with secondary data obtained from the annual reports of primary dealer banks listed on the Indonesia Stock Exchange during the 2016–2023 period. The results show that Corporate Governance has a significant positive effect on CSR disclosure, while Corporate Profitability has no significant effect. However, neither Corporate Governance nor CSR disclosure has a significant effect on Corporate Value. In contrast, Corporate Profitability has a significant positive effect on Corporate Value. Furthermore, CSR disclosure does not mediate the relationship between either Corporate Governance or Corporate Profitability and Corporate Value. These findings imply that profitability remains the main factor considered by investors in assessing firm value, while CSR is not yet perceived as a value-driving factor in the banking sector.